The Cause and Benefits of GDP - Bechtel, Gordon (Advances in Social Sciences Research Journal, 2021)
It has recently been shown that world GDP FP-Causes world life expectancy at birth, where FP denotes fractional polynomial (Bechtel, 2021). This article shows that American and Chinese GDPs FP-Cause world life expectancy even more strongly than world GDP does. These striking results beg the question: what FP-Causes American and Chinese GDPs? The answer is globalization, which is also shown here. Furthermore, it is demonstrated that American and Chinese GDPs also FP-Cause world literacy and employment rates. It remains to be seen if the World Bank or International Monetary Fund can show that the GDPs of the other (less affluent) 18 nations in the G20 Fp-cause their country’s life expectancy, as well as their literacy and employment rates. Yearly, pre-pandemic, within-nation increments in these variables can then be compared with subsequent decrements to assess an endogenous viral effect on each country’s well-being. These comparisons will expose inequalities across nations due to the varying wealth of nations. The results in this article are brought by Royston and Altman’s (1994) generalization of polynomial regression, which estimates both coefficients and their powers.